THE EVOLUTION OF ISLAMIC ARCHITECTURE IN TAMIL NADU: A HISTORICAL JOURNEY - Faheem Ahmad Dar; Rangarajan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Islamic architecture in Tamil Nadu was a unique synthesis of regional aesthetics and Islamic principles which give a rich confluence of diverse cultural and historical influences. From the grand mosques to the intricate tombs and minarets, Tamil Nadu's Islamic architecture showcases a blend of local craftsmanship and Islamic artistry. It highlights the role of Islamic architecture in shaping the region’s developed landscape, emphasizing the use of local materials and techniques that merge seamlessly with Islamic design and elements. By investigating these architectural spectacles, the study aims to illuminate the contributions of Islamic architecture to Tamil Nadu’s cultural heritage, revealing how it has adapted and thrived within a distinctive regional framework. This exploration not only enriches our understanding of Tamil Nadu’s architectural history but also underscores the enduring legacy of Islamic architectural innovation in South India. This study delves into the architectural marvels of Tamil Nadu, focusing on the interplay between indigenous Tamil and Islamic architectural styles.